Hacia una cartografía del dispositivo democrático global - Cuadro, Mariela (El Colegio de México A.C., 2019)
The starting point for this paper is the suspected existence of a globally functioning operational democratic mechanism. Based on the work of Michel Foucault, it conceives this mechanism as a network that links up heterogeneous elements and has the effect of producing subjectivities. By making methodological use of this mechanism, it links ethical propositions about freedom, theoretical constructions of international relations, political practices of states and international organizations, and normative constructions (specifically, the responsibility to protect) that accompany international interventions in the Global South, in order to reflect on the production of a democratic subject, the predicate of a global liberal government.